Evaluation of Commercial Enzyme-Linked Immunosorbent Assay Kits for Detection of Tuberculosis in Argentinean Population - Imaz, María Susana (American Society for Microbiology, 2004)
Pathozyme-Myco G (Myco G), M, A, and TB complex plus (Omega Diagnostics Ltd., Alloa, Scotland) were evaluated for the serological diagnosis of pulmonary tuberculosis (TB) in an Argentinean population. Sera from 58 patients with pulmonary TB, 24 subjects with pulmonary mycobacteriosis or mycoses (pulmonary MM group), and 45 subjects with other underlying disorders (control group) were analyzed. The sensitivities of the tests ranged from 29% (Myco M) to 82% (Myco G) in smear-positive patients (17 subjects) and from 29% (TB complex plus) to 49% (Myco G) in smear-negative patients (41 subjects). The specificities of the assays varied from 93% (Myco M) to 100% (Myco G and TB complex plus) in controls and from 62% (Myco A) to 96% (TB complex plus) in the pulmonary MM group. Overall, for the diagnosis of smear-negative patients, Myco G had the best characteristics, with a sensitivity of 49% and specificities of 100% for controls and 75% for the pulmonary MM group; after its combination with TB complex plus, its sensitivity improved to 59%. Nevertheless, despite its relatively poor capacity to discriminate between pulmonary TB and pulmonary MM, Myco G, alone or in combination with TB complex plus, would be a useful diagnostic tool for patients with suspected pulmonary TB living in areas where the relative prevalence of pulmonary MM was low.